Stacking Box Games to Stimulate Problem-Solving Skills in Children Aged 4-6 Years - Indrayanti, Dita; Chairani, Intan; Fadhilah Rizki, Nurul; Khoiriyah Amini, Rizqi; Sherly Utami, Winda; Surya Amanda, Rizki (Journal of Islamic Education Students (JIES), 2024)
This study aims to analyze the effect of using stacking box media in stimulating problem-solving skills in children aged 4-6 years at TK IT Fania Salsabila, focusing on the plant-themed application. The research employed a quantitative approach through observation and testing of the stacking box media. The study involved 17 children in a single class. Data were collected through observations during the trials and analyzed quantitatively, with results presented in tabular form. The findings indicate that the use of stacking box media significantly and positively impacts the development of problem-solving skills in children. This media is recommended as an innovative alternative for stimulating cognitive development in early childhood.